Growth Response of Pakcoy Cultivated in Biodegradable Bioplastic Polybags with Different Urea Contents - Syahriani Syahriani (Venn: Journal of Sustainable Innovation on Education, Mathematics and Natural Sciences, 2026)
The widespread use of conventional plastic polybags in vegetable cultivation contributes to persistent plastic waste because of their poor biodegradability, creating an increasing demand for environmentally friendly planting alternatives. This study evaluated the growth performance of pakcoy (Brassica rapa subsp. chinensis) cultivated in biodegradable bioplastic polybags containing different incorporated urea contents under greenhouse conditions. Bioplastic polybags previously developed in our laboratory were employed as planting containers, in which urea was incorporated as a controlled nutrient source, and their agronomic performance was evaluated through plant height, leaf width, number of leaves, and chlorophyll content after 28 days of cultivation. Plant growth varied according to the incorporated urea content. Among the evaluated formulations, the bioplastic polybag containing 0.75 g urea produced the highest plant height (10.2 cm), leaf width (5.1 cm), number of leaves (12 leaves), and chlorophyll content (45.2 SPAD units), indicating superior vegetative development compared with the other treatments. These findings suggest that an appropriate level of urea incorporation is more effective in supporting plant growth than either lower or higher urea contents. Overall, the developed biodegradable bioplastic polybags demonstrated promising potential as environmentally friendly planting containers for vegetable cultivation and provide a practical approach for developing sustainable biodegradable planting systems with integrated nutrient supply. Further studies under field conditions and using different horticultural crops are recommended to validate their broader agricultural applicability.